2010
DOI: 10.1113/jphysiol.2010.187682
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐ and age‐specific effects of nutrition in early gestation and early postnatal life on hypothalamo‐pituitary‐adrenal axis and sympathoadrenal function in adult sheep

Abstract: The early-life environment affects risk of later metabolic disease, including glucose intolerance, insulin resistance and obesity. Changes in hypothalamo-pituitary-adrenal (HPA) axis and sympathoadrenal function may underlie these disorders. To determine consequences of undernutrition in early gestation and/or immediately following weaning on HPA axis and sympathoadrenal function, 2-to 3-year-old Welsh Mountain ewes received 100% (C, n = 39) or 50% nutritional requirements (U, n = 41) from 1-31 days gestation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 80 publications
4
35
0
Order By: Relevance
“…Intriguingly, despite the decreased maternal weight gain during pregnancy, pups from calorie-restricted dams were not underweight at birth. These findings are consistent with other studies showing that the weight at birth could be unaffected when caloric restriction is implemented in the early stages of pregnancy (Sebert et al, 2009; Palou et al, 2010; Poore et al, 2010). The absence of differences in pups’ body weight may be associated to the significant increase in body weight and caloric intake of diet-restricted rat dams when the food restriction ended, which may have determined an accelerated weight gain in the fetus, as reported previously (Baik et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Intriguingly, despite the decreased maternal weight gain during pregnancy, pups from calorie-restricted dams were not underweight at birth. These findings are consistent with other studies showing that the weight at birth could be unaffected when caloric restriction is implemented in the early stages of pregnancy (Sebert et al, 2009; Palou et al, 2010; Poore et al, 2010). The absence of differences in pups’ body weight may be associated to the significant increase in body weight and caloric intake of diet-restricted rat dams when the food restriction ended, which may have determined an accelerated weight gain in the fetus, as reported previously (Baik et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with previous studies in humans, which demonstrated that offspring exposed to famine or hyperemesis gravidarum in the first part of pregnancy did not show lower birth weight (Roseboom et al, 2006; Grooten et al, 2015). Similarly, animal studies documented normoweight at birth when the early pregnancy was conducted under caloric restriction (Cleal et al, 2007; Palou et al, 2010; Poore et al, 2010). In contrast, a lower weight at birth has been described in several studies when the calorie-restricted diet was prolonged to birth (Desai et al, 2005; Lukaszewski et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…The sheep is especially interesting for pregnancy studies, due to singleton pregnancy and similar developmental trajectory to human beings [16]. Furthermore, the undernutrition during pregnancy in sheep has long-term effects on homeostasis and endocrine and cardiovascular systems [10,11,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%